Understanding children's perception of injury risk associated with playing sport. (1st March 2011) - White, P; Finch, C F; Dennis, R; Siesmaa, E
Abstract : Objective: Preventing sports injuries in children is important, but there is limited information about children's perceptions of injury risk or their injury beliefs and attitudes. This study investigates injury risk perceptions in a sample of junior sports participants across different age levels of play. Methods: Junior cricket players (n=284, aged 8–16) completed a reliable survey about their injury risk perceptions. Survey questions asked about players perceived injury risk to themselves compared to cricketers in general, as well as their perceived injury risk across different playing positions, ground conditions, and protective equipment use scenarios. Results: χ 2 analysis found age group differences in risk perceptions associated with different scenarios relating to playing position, ground conditions and protective equipment use. Players tended to see themselves as less likely to be injured than cricketers in general and perceived there to be a high risk of injury when fielding close to the batter and a comparatively low risk of injury when fielding in the outfield. Junior players also perceived there to be a high injury risk associated with playing on hard and bumpy grounds. Conclusions: Despite their relatively accurate perception of risk and appreciation for the importance of protective equipment, junior players need continual reminding of the importance of safety strategies by coaches and others. Coaches need to inform players that fielding injuries can occur anywhere on the ground, and include skills practice accordingly.